EXERGY ANALYSIS OF GEOTHERMAL POWER PLANT KAMOJANG 68, 3 MW IN CAPACITY - Aziz, Amiral (Jurnal Rekayasa Lingkungan)
The importance of exergy analysis in preliminary design of geothermal power has been proven. An exergy analysis was carried out and the locations and quantities of exergy losses, wastes and destructions in the different processes of the plan were pinpointed. The obtained results show that the total exergy available from production wells KMJ 68 was calculated to be 6967.55 kW. The total exergy received from wells which is connected during the analysis and enter into the separator was found to be 6337.91 kW in which 5808.8 kW is contained in the steam phase. The overall exergy efficiency for the power plant is 43.06% and the overall energy efficiency is 13.05 %, in both cases with respect to the exergy from the connected wells. The parts of the system with largest exergy destruction are the condenser, the turbine, and the disposed waste brinekeywords: exergy, irreversibility, geothermal power plant, KMJ 68